A New Hybrid Forecasting Strategy Applied to Mean Hourly Wind Speed Time Series. (11th June 2014) - Pappas, Stylianos Sp.; Karamousantas, Dimitrios Ch.; Chatzarakis, George E.; Pappas, Christos Sp.
Abstract : An alternative electric power source, such as wind power, has to be both reliable and autonomous. An accurate wind speed forecasting method plays the key role in achieving the aforementioned properties and also is a valuable tool in overcoming a variety of economic and technical problems connected to wind power production. The method proposed is based on the reformulation of the problem in the standard state space form and on implementing a bank of Kalman filters (KF), each fitting an ARMA model of different order. The proposed method is to be applied to a greenhouse unit which incorporates an automatized use of renewable energy sources including wind speed power.